INTRODUCTION TO ‟FORMS, FORMALISM AND UNIQUENESS (II) – THEMATIC DOSSIER” - RUSU, Mihai (Studia Universitatis Babeș-Bolyai Philosophia, 2018)
This dossier of Studia Universitatis Babeş-Bolyai. Philosophia gathers four papers written by early-career researchers that participated at the first edition of the ERGO Conference of Philosophy and Humanities. This conference took place at the Babeş-Bolyai University in April 2018 and it was organized as an integrative event, aimed at highlighting and capitalizing on the diverse landscape of philosophical research and education in Cluj-Napoca. The theme of this first meeting – Forms, Formalism and Uniqueness – was proposed so as to encourage reflection on the meaning and role of these concepts in the two main traditions of Western philosophy: continental and analytic. We expected that the contributions would be able to trace and characterize not only the multiple guises of these three concepts inside one tradition or the other, with their respective jargon and technicalities, but that we would also succeed in finding common points of interest and similar arguments and ideas that might inspire practitioners in either tradition and foster mutuality and actual collaboration. Our hopes were at least partially confirmed and I am certain there is much to look forward to from the young philosophers that participated in the event.